Assessing the place of neurobiological explanations in accounts of a family member's addiction. (31st August 2015) - Meurk, Carla; Fraser, Doug; Weier, Megan; Lucke, Jayne; Carter, Adrian; Hall, Wayne
Abstract: Introduction and Aims: The brain disease model of addiction posits that addiction is a persistent form of neural dysfunction produced by chronic drug use, which makes it difficult for addicted persons to become and remain abstinent. As part of an anticipatory policy analysis of addiction neuroscience, we engaged family members of addicted individuals to assess their views on the place and utility of brain‐based accounts of addiction. Design and Methods: Fifteen in‐depth qualitative interviews were conducted and used to develop a quantitative online survey that was completed by 55 family members. This article reports responses on what addiction is and how it is caused and responses to explanations of the brain disease model of addiction. Results: Participants gave multiple reasons for their family members developing an addiction and there was no single dominant belief about the best way to describe addiction. Participants emphasised the importance of both scientific and non‐scientific perspectives on addiction by providing multifactorial explanations of their family members' addictions. Most family members acknowledged that repeated drug use can cause changes to the brain, but they varied in their reactions to labelling addiction a 'brain disease'. They believed that understanding addiction, and how it is caused, could help them support their addicted relative. Discussion and Conclusions: Participants' beliefs about neurobiological information and the brain disease model of addiction appeared to be driven by empathetic, utilitarian considerations rather than rationalist ones. We discuss the importance of providing information about the nature and causes of addiction. [Meurk C, Fraser D, Weier M, Lucke J, Carter A, Hall W. Assessing the place of neurobiological explanations in accounts of a family member's addiction. Drug Alcohol Rev 2016;35:461–469]